If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14 + 3(x + 10) = 7(2 + 4) + x Reorder the terms: -14 + 3(10 + x) = 7(2 + 4) + x -14 + (10 * 3 + x * 3) = 7(2 + 4) + x -14 + (30 + 3x) = 7(2 + 4) + x Combine like terms: -14 + 30 = 16 16 + 3x = 7(2 + 4) + x Combine like terms: 2 + 4 = 6 16 + 3x = 7(6) + x Multiply 7 * 6 16 + 3x = 42 + x Solving 16 + 3x = 42 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 16 + 3x + -1x = 42 + x + -1x Combine like terms: 3x + -1x = 2x 16 + 2x = 42 + x + -1x Combine like terms: x + -1x = 0 16 + 2x = 42 + 0 16 + 2x = 42 Add '-16' to each side of the equation. 16 + -16 + 2x = 42 + -16 Combine like terms: 16 + -16 = 0 0 + 2x = 42 + -16 2x = 42 + -16 Combine like terms: 42 + -16 = 26 2x = 26 Divide each side by '2'. x = 13 Simplifying x = 13
| 33+3x+11x=33x | | 6+2x=3x+7+1-8 | | 5(12-3p)=1215p+60 | | -2(6-y)+4=-4 | | 9+3p-2=9p+25-4p | | x+-8=-8+3x | | 65m+50=45m+90 | | 8x+16=5x | | 90+.20x=50+.70x | | y-4x=17 | | 3x-12+4x-14=30 | | 2(2x-1)+3=9 | | 13=k/7 | | 7x-7=13+12 | | -61=d+[-18] | | 3(x+5)+3=3x+8 | | 8x-3=5+4(2x-2) | | 3-5x=10+x | | 4(-6)+10=2(n-7)-6 | | -11-7b=-7(b+2) | | -4(a-3)-(a+6)=1-8a+5+7a | | (3x-4)(2x+11)=0 | | -8+3-6x+6=-7x-2 | | 9x^2-17x-30= | | -8=-2+3/4x | | -3(4y-8)=-36 | | 30+5x+6x=30x | | 2x^4-128x=0 | | 351=3b | | 0.19y+0.05(y+7000)=2030 | | 3(-7a+6)-6a=-2a+18 | | Ax+r=5 |